The Community Manipulation through Big Brother’s Tyranny in George Orwell’s Nineteen Eighty Four - Devi Ismayanti; Andi Tenrisanna Syam (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research aimed on some instruments or agencies that implemented in constracting the community engineering in Orwell’s Nineteen Eighty Four, describe the logic used and present the community engineering carried out the novel. The writer then uses library research and sosiology literature as method in analyzing the novel. The data were collected by using note taking technique which exists in Nineteen Eighty-Four accord with the pages. Then, all the quotation classified and analyzed based on the case that had beeen arround by each moment/event in that novel. After doing the considerable study, the writer finds basically the bad effect of human engineering to the society. The over control by agents were bringing individuals’ loss of human nature and a critical thinking faculty and the diminished capacity for self expression. So, finally the human being is not exists as a human with high level values, in fact in this novel, human is less than the animal.